Wildervanck's syndrome with bilateral subluxation of lens and facial paralysis. Issue 1 (February 1983) - Strisciuglio, P; Raia, V; Di Meo, A; Rinaldi, E; Andria, G
Abstract : A 15-year-old female was found to have the typical features of Wildervanck's syndrome, including Klippel-Feil anomaly, abducens paralysis, retraction of the bulbi, and deafness. In addition, she had bilateral lens subluxation and facial paralysis, neither of which have been reported in patients with Wildervanck's syndrome.